Efficacy of Yangxin Recipe in Combination with Conventional Western Medicine in Treatment of Angina Pectoris of Coronary Heart Disease - Jiali Liu PhD; Yaorong Dong MD; Xiaozhen Hu PhD (Clinical and Applied Thrombosis/Hemostasis, 2022)
Objective To study the efficacy of Yangxin Recipe (YXR) in patients with stable angina pectoris of coronary heart disease and its impacts on coronary CT angiography. Methods A total of 78 patients with coronary heart disease and angina pectoris were randomly divided into a control group (n = 39) and a YXR group (n = 39). The control group adopted conventional Western medicine while the YXR group received conventional western medicine + oral administration of YXR. After six months of continuous treatment, the clinical efficacy, traditional Chinese medicine (TCM) syndrome scores, Pittsburgh Sleep Quality Index (PSQI), and the level of coronary CT vascular stenosis were observed. Results After treatment, the total effective rate of YXR was 92.31%, which was higher than ( P  < 0.01) that of the western medicine control group. The total score of TCM syndromes in the YXR group was (14.44 ± 9.87), which was significantly lower than ( P  < 0.001) that in the simple western medicine control group (22.44 ± 13.87). The degree of coronary stenosis in the YXR group decreased to (49.87 ± 7.82) %, which was significantly lower than ( P  < 0.001) that in the western medicine control group (57.05 ± 9.92) %. Conclusion The efficacy of YXR + conventional western medicine in treating coronary heart disease and angina pectoris is significantly improved compared with the simple conventional western medicine.